Blood pressure and kidney function in neonates and young infants with intrauterine growth restriction - Heuchel, Katharina Monika; Ebach, Fabian; Alsat, Ebru Aileen; Reutter, Heiko Martin; Mueller, Andreas; Hilger, Alina Christine (Pediatric Nephrology, 2022)
Background: Intrauterine growth restriction (IUGR) has been associated with changes in kidney anatomy, nephrogenesis and the vascular system, resulting in secondary arterial hypertension and kidney damage in adulthood. Here, we compare routine clinical and metabolic parameters between IUGR and non-IUGR study participants in the neonatal and early infant period. Methods: A total of 39 IUGR and 60 non-IUGR neonates were included during an 18-month study period. We compared blood pressure, serum creatinine (SCr), urea nitrogen (BUN), urinary albumin, α-1-microglobulin, transferrin, immunoglobulin G and total protein excretion in spontaneous urine normalized by urine creatinine level during the hospital stay. Results: There were no significant differences in mean values of blood pressure and urinary protein excretion between cases and controls. SCr and BUN levels were lower in the IUGR group compared to the non-IUGR group. Conclusions: The lower levels of SCr and BUN may be attributed to lower liver and muscle mass in IUGR neonates and young infants. Biomarkers currently used in routine clinical care do not allow early postnatal prediction of higher blood pressure or worse kidney function due to IUGR, so further studies are needed. Graphical abstract: A higher resolution version of the Graphical abstract is available as Supplementary information. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-09-16
Keywords: Blood pressure; Intrauterine growth restriction; Kidney function; Neonates; Proteinuria